A study of the interaction between grapevine vigour and water status for Vitis vinifera L. cv Merlot noir in Stellenbosch - Boshoff, Cornelis Johannes (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2010.